A new genus and species of an unusual Australian winter bee fly (Diptera: Bombyliidae) with discussion on its phylogenetic position. Issue 1 (2nd August 2018) - Li, Xuankun; Yeates, David K
Abstract: A new genus of bee fly (Bombyliinae: Bombyliini) is described to place a unique species Paramonovius nightking gen. et sp. nov. The new species is only collected in winter and is only known from a restricted area in Western Australia. Our morphological phylogeny indicates the new genus is sister to Sisyromyia White, 1916 and is similar to the latter in some external characters such as the one‐segmented antennal flagellum with apical stylus, subapex with 3–5 long hairs, open cell r 5 and cell br nearly as long as cell bm . However, Paramonovius gen. nov. has dichoptic male eyes, sparse scales on the median abdominal stripe, enlarged claw and pulvillus, as well as a series of autapomorphies in the genitalia. We present a modified key to the Australian genera of Bombyliini to accommodate this new genus. The unusual flight time of this genus may have contributed to its rarity in collections.